PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI, MOTIVASI, PROGRAM DIKLAT TERHADAP KINERJA, DAN KEPUASAN KERJA KARYAWAN - Andri, Seno; Troena, Eka Afnan; Idrus, Idrus; Djumahir, Djumahir (Jurnal Aplikasi Manajemen, 2011)
This study sould theoretically be used to develop the relevant theory and provide benefits in the implementation of the theory or practical. The finding of a causal relationship between the construct or latent variables are: 1) There is a significant positive effect on performance leadership of the force variable, 2) There is a significant positive effect on performance variables of organizational culture, 3) There is a significant positive effect of motivational variables on performance, 4) There is a significant positive influence of education and training variables of performance, 5) There is a significant positive influence on the leadership of the force variable job satisfaction, and 6) There are significant variables influence organizational culture affects job satisfaction.